Compatibility of Human Rights and Sharia: The Perspective of Interreligious Leaders in South and West Aceh Indonesia - Ikhwan, M. (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2023)
Human rights and Islamic law are two distinct sources of law with the common orientation of upholding the dignity of human beings. This study aimed to explore the compatibility of the two to avoid any conflicts and to ensure legal development that considers both human rights values and Islamic law, particularly in Aceh where Islamic law is implemented. The study began by asking two fundamental questions: how are human rights and Islamic law compatible in the context of legal development in Aceh? And how do interfaith figures in southwest Aceh view the compatibility of human rights and Islamic law? The study utilized qualitative research methods with a phenomenological approach and an interpretive paradigm, and it concluded with a continuous qualitative narrative analysis from the start of the research until its completion. The research findings indicate that human rights and Islamic law have been incorporated into the formulation of every law and can accommodate all segments of society in Aceh, both in terms of religion and humanity. Additionally, human rights and Sharia law in Aceh have found a point of convergence that is supported by the acceptance of cross-religious communities, particularly in southwestern Aceh. Thus, this research suggests that human rights and Sharia law are not in conflict with each other because they share the same orientation of respecting the dignity of humanity.